Characterization of the inhibition of hepatitis C virus entry by In vitro–generated and patient‐derived oxidized low‐density lipoprotein12. Issue 5 (15th February 2013) - Westhaus, Sandra; Bankwitz, Dorothea; Ernst, Stefanie; Rohrmann, Katrin; Wappler, Ilka; Agné, Clemens; Luchtefeld, Maren; Schieffer, Bernhard; Sarrazin, Christoph; Manns, Michael P.; Pietschmann, Thomas; Ciesek, Sandra; et al.
Abstract: Oxidized low‐density lipoprotein (oxLDL) has been reported as an inhibitor of hepatitis C virus (HCV) cell entry, making it the only known component of human lipid metabolism with an antiviral effect on HCV. However, several questions remain open, including its effect on full‐length cell‐culture–grown HCV (HCVcc) of different genotypes or on other steps of the viral replication cycle, its mechanism of action, and whether endogenous oxLDL shares the anti‐HCV properties of in vitro –generated oxLDL. We combined molecular virology tools with oxLDL serum measurements in different patient cohorts to address these questions. We found that oxLDL inhibits HCVcc at least as potently as HCV pseudoparticles. There was moderate variation between genotypes, with genotype 4 appearing the most oxLDL sensitive. Intracellular RNA replication and assembly and release of new particles were unaffected. HCV particles entering target cells lost oxLDL sensitivity with time kinetics parallel to anti‐SR‐BI (scavenger receptor class B type I), but significantly earlier than anti‐CD81, suggesting that oxLDL acts by perturbing interaction between HCV and SR‐BI. Finally, in chronically HCV‐infected individuals, endogenous serum oxLDL levels did not correlate with viral load, but in HCV‐negative sera, high endogenous oxLDL had a negative effect on HCV infectivity in vitro . Conclusion : oxLDL is a potent pangenotype HCV entry inhibitor that maintains its activity in the context of human serum and targets an early step of HCV entry. (HEPATOLOGY 2013)